Capacity Building Approach and Application: Utilization of Earth Observation Data and Geospatial Information Technology in the Hindu Kush Himalaya - Thapa, Rajesh Bahadur; Matin, Mir A.; Bajracharya, Birendra (Frontiers in Environmental Science, 2019)
While the Earth observation (EO) data and geospatial information technology (GIT) are getting more open and accessible, lack of skilled human resources and institutional capacities are limiting effective applications in the Hindu Kush Himalayan (HKH) region. This paper aims to present the capacity building approach and applications designed to fill these gaps and empower decision makers and practitioners through information education and training. The capacity building approach consists of four components: assessment, design, implementation and monitoring (ADIM). The assessment component focuses on identifying the needs and priorities of capacity building for targeted institutions. The design component develops training content in order to execute the plan in coordination with subject matter experts (SME). The implementation component executes the capacity building activity in any of these four formats – standard training, training of trainers, on-the-job training and exposure learning. The monitoring component helps to identify the participants’ expectations, learning achievements and feedback to improve capacity building events. In the application of ADIM, we conducted needs assessment in four countries, designed 26 types of capacity building contents and implemented 39 capacity building events. A range of thematic topics – from agriculture and food security, water resources and hydro-climatic disasters, land use, land cover and ecosystem, weather and climate services, to crosscutting issues – were covered in the events. Altogether, the activities reachedout 1,000+ individuals (35% of them women) from 200+ unique institutions in 30 countries. Institutional capacity was built for universities in Afghanistan and Bangladesh to design and deliver courses independently. The capacity of partner agencies were built to co-design and co-develop data and applications. The approach also experienced challenges in the nomination process and in identifying women participants due to the lack of women professionals in the field and in the respective agencies. The ADIM approach and its workflow focused on bridging the gap between the current trend and progression in EO and GIT fields and the existing state of capacity of the agencies involved in the decision-making process. It promoted gender equity, adopted frontier technologies, engaged SMEs and provided sustainable solutions, which are starting to bring success stories in the region.